Isolation, identification and serotyping of Pasteurella multocida isolates from pneumonic lungs of pigs and sensitivity to several their antibiotics - Chotiah, Siti (Indonesian Animal Sciences Society, 1997)
Six isolates of Pasteurella multocida were recovered from 105 pneumonic lungs of pigs, collected from a pig slaughter house at Kapuk, West Jakarta and two piggeries in Tangerang, West Java. The identification and serotyping of the isolates based on the differences of their capsular antigenic, using indirect haemagglutination method, showed that five isolates were type A and one isolate was type D. Using the isc method, in vitro sensitivity of the isolates to seven kinds of antibiotics showed that all of the isolates were sensitive to nalidixic acid (NA 30 pg), enrofloxacin (ENR 5 pg), gentamycin (GN 10 gg), and sulphamethoxazole trimethoprim (SXT 25 pg), while five isolates were sensitive to doxycycline hydrochloride (DO 30 gg), four isolates were sensitive to erythromycin (E 15 pg), and two isolates were sensitive to tetracycline (TE 15 pg) . Â Key words : Pasteurella multocida, pig, serotyping, antibiotics